MARKETING PROMOTION OF INNOVATIVE ACTIVITIES – THE EXAMPLE OF THE RENEWABLE ENERGY RESOURCES SECTOR (RES) IN THE LUBLIN REGION - Magdalena Rzemieniak (Polityki Europejskie, Finanse i Marketing, 2015)
The development of the Lubelskie Province should be focused on strategic fields of economy of Poland and the Province. The entrepreneurship growth among the Lubelskie Province citizens may stimulate the mainspring of development1. The rational usage of energy from the so called renewable sources, i.e. river, wind, solar rays, geothermal energy and biomass, is one of the vital components of sustainable development and brings measurable ecological and energy effects. The growing participation of the RES in the world energy and fuel balance contributes to the usage and saving efficiency of energy resources. It also improves the condition of the environment through reducing the emission of pollution to waters and atmosphere and reducing the amount of produced waste. The Province development strategy should include the development of the production from the renewable sources, the usage of regional energy sources, the promotion of ecoenergy among the end-users and the development of research and implementation activity. These activities require conscious, purposeful and professional promotional actions aimed at diversified target groups and stakeholders. The aim of this article is to show the impact of promotional activities on the development of the sector of Renewable Energy Sources (RES), as well as an in-depth analysis and review of the available documentation regarding activities that promote the RES sector. This work puts forward the following hypothesis: customized promotional activities are essential for effective development of the RES sector. The research methods used in this study include desk research, carried out on secondary sources (both internal and external), participant observation (as an expert of the Lublin City Office and the Marshal’s Office of the Lubelskie Province in Lublin) and non-participant observation. The research was carried out between January and June 2015.